Low-frequency absorption cross section of the electromagnetic waves for extreme Reissner-Nordström black holes in higher dimensions - Crispino, Luís C. B.; Higuchi, Atsushi; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2010)
We investigate the low-frequency absorption cross section of the electromagnetic waves for extreme Reissner-Nordström black holes in higher dimensions. We first construct the exact solutions to the relevant wave equations in the zero-frequency limit. In most cases it is possible to use these solutions to find the transmission coefficients of partial waves in the low-frequency limit. We use these transmission coefficients to calculate the low-frequency absorption cross section in five and six spacetime dimensions. We find that this cross section is dominated by the modes with ℓ=2 in the spherical-harmonic expansion rather than those with ℓ=1, as might have been expected, because of the mixing between the electromagnetic and gravitational waves. We also find an upper limit for the low-frequency absorption cross section in dimensions higher than six. © 2010 The American Physical Society.